2011
DOI: 10.1021/es201308x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Process- and Input–Output-based Life Cycle Inventory Data with Regard to Truncation and Aggregation Issues

Abstract: Life cycle assessments (LCA) and environmentally extended input-output (EEIO) analyses both strive to account for direct and indirect environmental impacts of goods and services. Different methods have been developed to hybridize these two techniques and minimize the impact of their respective shortcomings on final assessments. These weaknesses, however, have not been extensively studied in a quantitative manner, especially not for complete LCA and EEIO databases. To this end, we jointly analyzed process-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
176
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(188 citation statements)
references
References 39 publications
(74 reference statements)
1
176
0
4
Order By: Relevance
“…However, the current survey demonstrates that hybrid LCA studies on wind power are still relatively scarce -this fits into a general trend that despite its acknowledged advantages, hybrid techniques have not yet become standard practice in LCA [10]. Hybrid LCA is more challenging to conduct and requires additional data, which may be an explanation for its lack of use.…”
Section: Methods For Life Cycle Inventory and System Boundary Issuesmentioning
confidence: 97%
See 3 more Smart Citations
“…However, the current survey demonstrates that hybrid LCA studies on wind power are still relatively scarce -this fits into a general trend that despite its acknowledged advantages, hybrid techniques have not yet become standard practice in LCA [10]. Hybrid LCA is more challenging to conduct and requires additional data, which may be an explanation for its lack of use.…”
Section: Methods For Life Cycle Inventory and System Boundary Issuesmentioning
confidence: 97%
“…While there is no consensus in the LCA community on how to measure the truncation bias of process-LCA, in all explorations into this issue surveyed by MajeauBettez et al [10] it is found that process-LCA fails to account for 30% or more of total indicator values. This predicates that the employment of hybrid LCA methodologies should be a goal of future LCA research on wind power; and that if hybrid techniques on the other hand are not applied, the problem of cut-off errors should at the least be recognized -in existing literature this is not the case.…”
Section: Methods For Life Cycle Inventory and System Boundary Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…An EIO analysis is a "top-down" approach, capable of capturing impacts from the entire supply chain and is useable as a screening tool to inform estimation of the anticipated life cycle emissions [2]. However, the approach is also criticised, mainly for being too aggregated, thus causing the need to hybridize with "bottom-up" data collection, where the generic EIO model is evaluated as being insufficient [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%